A multi-country cross-sectional study of self-reported sexually transmitted infections among sexually active men in sub-Saharan Africa - Abdul-Aziz Seidu; Bright Opoku Ahinkorah; Louis Kobina Dadzie; Justice Kanor Tetteh; Ebenezer Agbaglo; Joshua Okyere; Tarif Salihu; Kenneth Fosu Oteng; Eustace Bugase; Sampson Aboagye Osei; John Elvis Hagan; Thomas Schack (BMC, 2020)
Abstract Background Despite the importance of self-reporting health in sexually transmitted infections (STIs) control, studies on self-reported sexually transmitted infections (SR-STIs) are scanty, especially in sub-Saharan Africa (SSA). This study assessed the prevalence and factors associated with SR-STIs among sexually active men (SAM) in SSA. Methods Analysis was done based on the current Demographic and Health Survey of 27 countries in SSA conducted between 2010 and 2018. A total of 130,916 SAM were included in the analysis. The outcome variable was SR-STI. Descriptive and inferential statistics were performed with a statistical significance set at p < 0.05. Results On the average, the prevalence of STIs among SAM in SSA was 3.8%, which ranged from 13.5% in Liberia to 0.4% in Niger. Sexually-active men aged 25-34 (AOR = 1.77, CI:1.6-1.95) were more likely to report STIs, compared to those aged 45 or more years. Respondents who were working (AOR = 1.24, CI: 1.12-1.38) and those who had their first sex at ages below 20 (AOR = 1.20, CI:1.11-1.29) were more likely to report STIs, compared to those who were not working and those who had their first sex when they were 20 years and above. Also, SAM who were not using condom had higher odds of STIs (AOR = 1.35, CI: 1.25-1.46), compared to those who were using condom. Further, SAM with no comprehensive HIV and AIDS knowledge had higher odds (AOR = 1.43, CI: 1.08-1.22) of STIs, compared to those who reported to have HIV/AIDS knowledge. Conversely, the odds of reporting STIs was lower among residents of rural areas (AOR = 0.93, CI: 0.88-0.99) compared to their counterparts in urban areas, respondents who had no other sexual partner (AOR = 0.32, CI: 0.29-0.35) compared to those who had 2 or more sexual partners excluding their spouses, those who reported not paying for sex (AOR = 0.55, CI: 0.51-0.59) compared to those who paid for sex, and those who did not read newspapers (AOR = 0.93, CI: 0.86-0.99) compared to those who read. Conclusion STIs prevalence across the selected countries in SSA showed distinct cross-country variations. Current findings suggest that STIs intervention priorities must be given across countries with high prevalence. Several socio-demographic factors predicted SR-STIs. To reduce the prevalence of STIs among SAM in SSA, it is prudent to take these factors (e.g., age, condom use, employment status, HIV/AIDS knowledge) into consideration when planning health education and STIs prevention strategies among SAM.